A Multi-modal Deep Learning Approach for Predicting Type 2 Diabetes Complications: Early Warning System Design and Implementation - Xiong, Ke; Cao, Guanghe; Jin, Meizhizi; Ye, Biao (Journal of Theory and Practice of Engineering Science, 2025)
This paper presents a novel multi-modal deep learning framework for early prediction of Type 2 Diabetes (T2D) complications through an advanced early warning system. The proposed architecture integrates multiple data modalities including clinical measurements, laboratory results, and temporal patient data through a sophisticated attention-based fusion mechanism. The system implements specialized preprocessing techniques for different data modalities and employs an innovative feature extraction pipeline for comprehensive risk assessment. Experimental validation was conducted on a dataset comprising 15,847 patients collected over five years from multiple medical centres. The framework achieved 94.7% prediction accuracy with a 72-hour warning window, demonstrating superior performance compared to existing approaches. The implementation of adaptive threshold mechanisms reduced false positive rates to 4.8% while maintaining 93.8% sensitivity and 95.2% specificity. The system's effectiveness was validated through prospective testing on an independent cohort of 3,245 patients, showing robust performance across diverse patient populations. The attention-based fusion mechanism demonstrated a 15% improvement in prediction accuracy compared to conventional approaches. This research contributes to the advancement of medical artificial intelligence through interpretable deep learning models, providing healthcare practitioners with insights into the decision-making process while maintaining high prediction accuracy for early intervention in T2D complications management.